Proposals for WTO Reform : A Synthesis and Assessment - Hoekman, Bernard (2012)
This paper summarizes the major arguments and proposals to reform the modus operandi of the World Trade Organization --including decision-making procedures, negotiating modalities, and dispute settlement. Much has already been done to improve the internal and external transparency of World Trade Organization processes. Some proposals for structural reform ignore incentive constraints and the fact that the World Trade Organization is an incomplete contract that must be self-enforcing. Others -- such as calls for a "critical mass" approach to negotiations --can already be pursued (and have been). The agenda for international cooperation increasingly revolves around "behind-the-border" regulatory externalities that do not necessarily lend themselves to binding commitments in a trade agreement. This suggests a focus on strengthening notification/surveillance and developing more effective mechanisms for dialogue on regulatory policies that may create negative spillovers.